Vitamin D Inhibits IL-22 Production Through a Repressive Vitamin D Response Element in the il22 Promoter - Lopez, Daniel V.; Al-Jaberi, Fatima A.H.; Damas, Nkerorema D.; Weinert, Brian T.; Pus, Urska; Torres-Rusillo, Sara; Woetmann, Anders; Ødum, Niels; Bonefeld, Charlotte M.; Kongsbak-Wismann, Martin; Geisler, Carsten (Frontiers in Immunology, 2021)
Th22 cells constitute a recently described CD4+ T cell subset defined by its production of interleukin (IL)-22. The action of IL-22 is mainly restricted to epithelial cells. IL-22 enhances keratinocyte proliferation but inhibits their differentiation and maturation. Dysregulated IL-22 production has been associated to some inflammatory skin diseases such as atopic dermatitis and psoriasis. How IL-22 production is regulated in human T cells is not fully known. In the present study, we identified conditions to generate Th22 cells that do not co-produce IL-17 from naïve human CD4+ T cells. We show that in addition to the transcription factors AhR and RORγt, the active form of vitamin D (1,25(OH)2D3) regulates IL-22 production in these cells. By studying T cells with a mutated vitamin D receptor (VDR), we demonstrate that the 1,25(OH)2D3-induced inhibition of il22 gene transcription is dependent on the transcriptional activity of the VDR in the T cells. Finally, we identified a vitamin D response element (VDRE) in the il22 promoter and demonstrate that 1,25(OH)2D3-VDR directly inhibits IL-22 production via this repressive VDRE.